Whole Exome Sequencing in a Population With Severe Congenital Anomalies of Kidney and Urinary Tract - Harris, Meredith; Schuh, Meredith P.; McKinney, David; Kaufman, Kenneth; Erkan, Elif (Frontiers in Pediatrics, 2022)
Fetal and neonatal interventions (e.g., amnioinfusions, amniotic shunting and infant dialysis) have increased survival of infants with severe Congenital Anomalies of the Kidney and Urinary Tract (CAKUT), however, outcomes vary dramatically. Our aim was to perform Whole Exome Sequencing (WES) in a unique severe CAKUT population with the goal to identify new variants that will enhance prediction of postnatal outcomes. We performed trio whole exome sequencing (WES) on 5 infants with severe CAKUT (undergoing fetal interventions and/or those who initiated renal replacement therapy (RRT) within one month of life) and their parents as well as 3 singletons. We identified 3 potential candidate gene variants (NSUN7, MTMR3, CEP162) and validated two variants in known CAKUT genes (GATA3 and FRAS1) showing strong enrichment in this severe phenotype population. Based on our small pilot study of a unique severe CAKUT population, WES appears to be a potential tool to help predict the course of infants with severe CAKUT prenatally.